2023
DOI: 10.3389/fendo.2023.1227489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercises in prediabetes patients: a systematic review and meta-analysis

Abstract: AimsTo evaluate the effects of different durations of continuous aerobic exercise on prediabetic patients.Materials and methodsThe research encompassed randomized controlled trials that examined how various durations of aerobic exercise training affected outcomes related to Body Mass Index (BMI), Fasting blood glucose (FBG), 2-hour plasma glucose (2hPG), and glycated hemoglobin (HbA1c) in individuals diagnosed with prediabetes. PubMed, Embase, Web of Science, and the Cochrane Library were searched as of Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Physical activity has a positive impact on reducing glycemia, improving insulin resistance, and decreasing body weight [30,47,48]. In this study, the control group increased CRP and IL-6 levels, whereas the RD group significantly decreased these levels in 12 weeks.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Physical activity has a positive impact on reducing glycemia, improving insulin resistance, and decreasing body weight [30,47,48]. In this study, the control group increased CRP and IL-6 levels, whereas the RD group significantly decreased these levels in 12 weeks.…”
Section: Discussionmentioning
confidence: 52%
“…Wang et al reported that participating in aerobic exercise could significantly lower glucose levels in individuals with prediabetes. Additionally, this might result in declines in BMI, FBG, 2hPG, HbA1c, and other relevant markers [48]. A previous study reported that Yijinjing, traditional Chinese exercise combined with resistance training, could improve fasting blood glucose, insulin resistance, and reduce liver fat in middle-aged and older people with prediabetes [49].…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, aerobic training can enhance both blood pressure control ability and insulin secretion two hours after consuming a meal. Several metaanalyses and RCTs have also confirmed that vigorous-intensity aerobic exercise significantly improves 2hPG levels, particularly in patients with IGT (35,58,59). Aerobic exercise increases peak oxygen consumption and can improve glucose tolerance, whole-body insulin sensitivity, and cardiovascular adaptation (32).…”
Section: Comparisons With Previous Studiesmentioning
confidence: 91%
“…Exercise may have an immediate though transient anxiolytic 8 and even euphoric 9 effect. Exercise has been shown to improve subjective well-being 10 and healthrelated quality of life 11 ; reduce anxiety, 12 depression, 13 and suicide attempts 14 ; improve sleep 15 ; improve cognitive test performances 16 ; improve sexual functioning 17 ; improve pregnancy outcomes 18 ; reduce the severity of chronic pain 19 ; improve bone mineral density 20 and reduce the risk of falls 21 and fractures 22 ; reduce cardiometabolic risk factors such as overweight and obesity, 23 dyslipidemia, 24 and hypertension 25 ; improve metabolic outcomes in prediabetes 26 and diabetes 27 ; reduce the risk of infection and mortality therefrom 28,29 ; reduce the risk of different cancers 30,31 ; reduce the risk of neurodegenerative disorders such as Parkinson 32 and Alzheimer disease 33 ; reduce cardiovascular 34 and cerebrovascular 35 disease events in both primary and secondary prevention 36 ; reduce the risk of heart failure 37 ; and reduce cancer, cardiovascular, and all-cause mortality. 3 This list is not comprehensive.…”
Section: Exercise: Benefitsmentioning
confidence: 99%